2018
DOI: 10.1017/s153759271700425x
|View full text |Cite
|
Sign up to set email alerts
|

From Backwaters to Major Policymakers: Policy Polarization in the States, 1970–2014

Abstract: Political scientists often characterize state and local governments as marginal and highly constrained in policymaking. However, I suggest that in recent decades state governments have moved from the margins to the center of partisan battles over the direction of U.S. public policy. Across 16 issue areas, I investigate interstate policy variation, policy differences across states, and policy polarization, the changing relationship between party control of state government and policy outcomes. Since the 1970s, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
174
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 160 publications
(180 citation statements)
references
References 77 publications
2
174
1
Order By: Relevance
“…Recent evidence has demonstrated that, since the 1970s, the policy context in which Americans live is increasingly determined by their state of residence. 21,22 This new reality was spurred by two significant changes in the balance of policymaking authority across federal, state, and local governments. First, the decentralization of policymaking authority from federal to state levels (termed "devolution") gave states greater discretion over programs such as welfare and Medicaid by replacing categorical grants to states with block grants that had few strings attached.…”
Section: Importance Of Structural Explanationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent evidence has demonstrated that, since the 1970s, the policy context in which Americans live is increasingly determined by their state of residence. 21,22 This new reality was spurred by two significant changes in the balance of policymaking authority across federal, state, and local governments. First, the decentralization of policymaking authority from federal to state levels (termed "devolution") gave states greater discretion over programs such as welfare and Medicaid by replacing categorical grants to states with block grants that had few strings attached.…”
Section: Importance Of Structural Explanationsmentioning
confidence: 99%
“…To answer this question, we use a recently created, extensive data set of state-level policies, where each policy is measured on a conservative-liberal continuum. 21 The second question is hypothetical: how might US longevity change if all states enacted policy contexts that were liberal or conservative, or that mirrored the states with the largest or smallest shifts in policy context between 1970 and 2014? This study State policy scores are from Grumbach, 21 and state life expectancy data are from the United States Mortality Database.…”
Section: Importance Of Structural Explanationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interest group scholars also point to partisanship and ideology as constraints on interest group influence (e.g., Leech 2010), and at the subnational level, these forces either vary across contexts or are weaker across the board. States, for example, vary in the extent of their elite polarization (Shor and McCarty 2011), and there are at least some important state issues that are not intensely partisan, such as public pensions and criminal justice (Anzia and Moe 2017;Grumbach 2018). Local politics tends to be even less partisan and ideological: most local 14 elections are non-partisan, and the issues that define local politics are custodial rather than ideological in nature (Oliver 2012).…”
Section: Interest Group Influencementioning
confidence: 99%
“…At the state level, there are datasets of registered lobbyists and campaign contributions, but anyone wishing to research interest groups' activity beyond those forms has to collect new data (e.g., Anzia and Moe forthcoming; Hertel-Fernandez forthcoming). Scholars are starting to do more to assemble and analyze data on state policies (e.g., Caughey et al 2017;Grumbach 2018), but so far little has been done to use data on state policies to study interest group influence. The situation is worse at the local level, where not only are there no existing datasets of interest group activity, but there also aren't many readily available datasets of local policies beyond public finance outcomes.…”
Section: Caveats and Conclusionmentioning
confidence: 99%